FEATURES OF ACCOUNTING OF PRODUCTS OF FORESTRY ENTERPRISES - ISHCHENKO, Yana; ARMIDER, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The publication is devoted to the study of the features of accounting for forestry enterprises' products. The paper examines key aspects of accounting processes that accompany the production activities of forestry enterprises, in particular methodological approaches to assessing and accounting for products, taking into account the specifics of the industry. The purpose of this publication is to study the processes of accounting for forestry products at all stages of production business processes, as well as to develop recommendations for improving the organization and methodology of accounting for forestry products. To form an accounting system for the production process of forestry products, production costs are classified according to various characteristics. The classification of production costs for forestry products is generalized. The business processes of the production activities of forestry enterprises are identified. It is proposed to separate objects of accounting for production costs using the process method and sub-accounts for reflecting the costs of main production in terms of business processes, which will allow obtaining relevant information about each stage of the production process for optimizing and reengineering business processes. The methodology for accounting for forestry products is generalized depending on the option of its assessment at initial recognition. The objective need for adapting accounting legislation to the needs and requests of forest industry management and for the formation of a unified methodology for accounting for forestry enterprises is substantiated. The conducted research revealed a number of important aspects that require further development and improvement in the field of forest product accounting. In particular, improving regulatory and legal regulation, integrating the accounting system with innovative information systems used in managing business processes in the forestry industry.
Keywords: forestry; finished products; forestry enterprises; accounting; cost items; evaluation of finished products